Монастирі ХІІ – першої половини ХІІІ ст. на правобережжі Середнього Дністра - Возний, Ігор (Матеріали і дослідження з археології Прикарпаття і Волині. Вип. 22. – Львів: Інститут українознавства ім. І. Крип’якевича НАН України, 2018)
MONASTERIES IN THE XII – THE FIRST HALF OF THE XIII CENTURY ON THE RIGHT BANK OF THE MIDDLE DNISTER Ihor VOZNYJ Yuriy Fedkovych Chernivtsi National University, Kotsjubynskyi St., 2, 58012, Chernivtsi, Ukraine, e-mail: voznyj_igor@rambler.ru The article considers the problem of the formation and evolution of Christian monasteries in the cities of the right bank of the Middle Dnister. Whereas the black clergy was very significant in their layer. The Monasteries on the specified territory, as well as on the territory of South-West Rus, appeared in the middle of the XII century. It is shown their importance as a part of the city in spreading the Christian ideology. Also were considered the cave monasteries of the Dnister canyon. The cave monasteries began to operate in the Dnister canyon already from XIth, as it was indicated by the group of researchers. As the first “Cloister” for the monks served the rock shelters, mainsails, caves, widely represented in the Ukrainian Carpathian Mountains. For the installation of the monasteries usually are used the group of the caves and separately placed underground cavities could be settled by the the desert monks who were associated with Byzantine monastic traditions. The structure of the monastery could include the settlements. Probably the monasteries of XII – early XIII century owned so many lands with attached peasants, which was required only to meet their needs and not for benefication. The Orthodox Monasteries of the XII – early XIII century were placed in the territory of ancient rusian cities or in nearby suburbs. Therefore, these sacral objects should be taken as a essential sign that a one or another inhabited locality in XII – early XIII century was a real city. In ancient rusian cities the black clergy in addition to its core missionary activities led an active social life.
Keywords: monastery; black clergy; yeremit monasteries; kenovian monasteries; cave monasteries; Zenkivtsi on Prut river; Vasyliv; Kuchelmin